Evolution mechanism of wave velocity and mechanical properties in coal samples under water-saturated and cyclic stress coupling effects - Jie LI (Meikuang Anquan, 2025)
In deep coal mining, the influence of hydro-mechanical coupling on coal mechanical properties is a critical factor inducing dynamic disasters. To reveal the damage evolution law of coal under water saturation and cyclic stress disturbance, this study systematically investigated the wave velocity, deformation, strength, and failure characteristics of natural coal samples (Group A), water-saturated coal samples (Group B), and cyclic stress-disturbed coal samples (Group C) through ultrasonic testing, conventional triaxial compression tests, and CT scanning. The results indicate that water saturation effect reduces acoustic wave scattering by filling pores, increasing the longitudinal wave velocity by 18.2% (Group B), however, the cyclic stress disturbance triggers the micro-fracture expansion and the “water-fracture coupling effect”, resulting in a 4.44% decrease in the wave velocity of Group C compared with the natural group; hydro-mechanical coupling action significantly alters deformation mechanisms: water saturation shortens the compaction stage and weakens yield strength (reduced elastic modulus in Group B), whereas cyclic disturbance induces post-peak stress stepwise decline and residual strength enhancement, and its energy dissipation characteristics are similar to the mechanism of “self-supporting cracks”; both water saturation and cyclic stress degrade coal strength, the peak strength of the saturated water group (decreased by 28.0%) and the cyclic disturbance group (decreased by 33.0%) was significantly lower than that of the natural group. However, the confining pressure sensitivity of the cyclic disturbance samples was the strongest (the strength increased by 174.8% with the confining pressure), indicating that the damaged coal body can restore part of its bearing capacity through confining pressure constraints; hydro-mechanical coupling action leads to different failure modes of coal body. The water-saturated coal samples were mainly subjected to shear failure, while the cyclically disturbed coal samples formed multi-directional fracture zones and lateral expansion. The accumulation of damage was dominated by the “water wedge effect” and fatigue crack propagation, and the shear-tensile combined failure intensified after confining pressure unloading.